2005
DOI: 10.1038/sj.gt.3302541
|View full text |Cite
|
Sign up to set email alerts
|

In vivo NMR imaging evaluation of efficiency and toxicity of gene electrotransfer in rat muscle

Abstract: In vivo gene electrotransfer (ET) is a simple method of gene delivery in various tissues relying on the injection of plasmid DNA followed by application of electric pulses. Noninvasive tools are needed to evaluate the ET efficiency and the resulting tissue damages. In this study, we performed ET of rat tibialis muscle after injection of either a plasmid coding for luciferase or a contrast agent (CA) detected by using magnetic resonance imaging (MRI). Plasmid expression and CA intracellular trapped quantity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…While histologic measurements were highly correlated with intraprocedural rigorously investigate the mechanism or mechanisms that may have lead to these aforementioned differences. membranes, during which muscle tissue edema was visualized as hyperintense regions on T2-weighted images ( 4,29 ).…”
Section: Discussionmentioning
confidence: 99%
“…While histologic measurements were highly correlated with intraprocedural rigorously investigate the mechanism or mechanisms that may have lead to these aforementioned differences. membranes, during which muscle tissue edema was visualized as hyperintense regions on T2-weighted images ( 4,29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, increasing the energy of the applied pulses also increases their adverse effects on tissues. Therefore, the higher energy pulses, which may result in an irreversible cell membrane modification [41,42], are unlikely to be suitable for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also shown that muscle necrosis increases with the cumulative duration of the pulses [Mathiesen, 1999]. Recently, an in vivo NMR imaging system has been developed to visualize and evaluate the electropermeabilized zones during electric field-mediated drug or gene delivery [Leroy-Willig et al, 2005] and therefore assess more precisely the efficiency and toxicity of different protocols.…”
Section: Dna Electrotransfer and Toxicitymentioning
confidence: 99%
“…The procedure itself (needle injection and cell permeabilisation by high electric field) may induce an inflammatory response [Leroy-Willig et al, 2005], but this inflammation has been shown to be mostly plasmid DNA-dependent [Hartikka et al, 2001]. Plasmid DNA stimulates the immune system and leads to inflammation via the hypomethylated bacterial CpG sequences, via the antibiotic resistance genes and promoter elements containing prokaryotic immunostimulatory sequences, and possibly even via contamination during the plasmid purification process, with LPS for example [McMahon et al, 1998].…”
Section: Dna Electrotransfer and Toxicitymentioning
confidence: 99%